Infectious complications of shunt systems in children from the region of upper silesia treated in the years 2000-2010 - Zygmunt, Agata Dominika; Szefczyk-Polowczyk, Lucyna; Mandera, Marek (Journal of Education, Health and Sport, 2015)
Zygmunt Agata, Szefczyk-Polowczyk Lucyna, Mandera Marek. Infectious complications of shunt systems in children from the region of upper silesia treated in the years 2000-2010. Journal of Education, Health and Sport. 2015;5(5):205-212. ISSN 2391-8306. DOI 10.5281/zenodo.17590 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%285%29%3A205-212 https://pbn.nauka.gov.pl/works/559813 http://dx.doi.org/10.5281/zenodo.17590 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 – 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 15.02.2015. Revised 27.04.2015. Accepted: 08.05.2015. INFECTIOUS COMPLICATIONS OF SHUNT SYSTEMS IN CHILDREN FROM THE REGION OF UPPER SILESIA TREATED IN THE YEARS 2000-2010 Agata Zygmunt1, Lucyna Szefczyk-Polowczyk2, Marek Mandera3 1Studium Doktoranckie, Wydział Lekarski, Śląski Uniwersytet Medyczny w Katowicach 2Studium Doktoranckie, Wydział Farmaceutyczny z Oddziałem Medycyny Labolatoryjnej, Śląski Uniwersytet Medyczny w Katowicach 3Klinika Neurochirurgii Dziecięcej Szpitala Klinicznego Nr 6 Śląskiego Uniwersytetu Medycznego Górnośląskiego Centrum Zdrowia Dziecka w Katowicach Pierwszy autor: Agata Zygmunt Adres do korespondencji: Katowice 40-477 ul. Gościnna 5d/24 Tel kontaktowy: 668 068 676 Adres e-mail: agatamucha85@gmail.com Abstract Introduction. Infections of shunt systems are still a major problem in pediatric neurosurgery. They are the cause of 19% of all revision within 10 years of implantation of the shunt. Aim. The aim of the study was infectious complications in patients of the Pediatric Neurosurgery operated on for hydrocephalus in 2000-2010 in Katowice. Material and methods. In order to implement the above assumptions medical records were reviewed of patients hospitalized in the Pediatric Neurosurgery in Katowice in the years 2000 - 2010. Results. First shunt implantation were performed in children under the 3 months of age. Infectious complications occurred in 5.2% of patients operated on for hydrocephalus in 10 years. Conclusion. Shunt system infections occurred most often in children up to the age of 6 months. The most common infectious agent in the test was staphylococcus epidermidis. Key words: infection, shunt system, the etiological agent, shunt implantation, infectious complications.